Decreased Opioid Consumption and Length of Stay Using an IPACK and Adductor Canal Nerve Block following Total Knee Arthroplasty - Eccles, Christian J.; Swiergosz, Andrew M.; Smith, Austin F.; Bhimani, Samrath J.; Smith, Langan S.; Malkani, Arthur L. (The Journal of Knee Surgery, 2019)
Peripheral nerve blocks such as a femoral + sciatic block have demonstrated significant pain relief following TKA. However, these nerve blocks have residual motor deficits which prevent immediate postoperative ambulation. The purpose of this study was to compare outcomes in patients undergoing primary TKA with femoral and sciatic (Fem + Sci) motor nerve blocks versus an adductor canal and the interspace between the popliteal artery and the capsule of the posterior knee and adductor canal block (IPACK + ACB) sensory nerve blocks. A total of 100 consecutive patients were reviewed, 50 received Fem + Sci nerve blocks and 50 received IPACK + ACB blocks preoperatively. There were no differences in the two groups with respect to surgical technique, implant type, postoperative pain, and physical therapy protocols. Differences in opioid requirements, length of stay (LOS), distance walked, and common knee scoring systems were analyzed. Among them, 62% IPACK + ACB patients were discharged on postoperative day 1 compared with 14% in the Fem + Sci group (p < 0.0001). The IPACK + ACB patients had a shorter LOS (mean 1.48 days vs. 2.02 days, p < 0.001), ambulated further on postoperative day 0 (mean 21.4 feet vs. 5.3 feet, p < 0.001), and required less narcotics the day after surgery (mean, 15.7 vs. 24.0 morphine equivalents p < 0.0001) and at 2 weeks (mean, 6.2 vs. 9.3 morphine equivalents, p = 0.025). The use of this combination IPACK and ACB demonstrated improved early ambulation with a decrease in opioid use and length of stay compared with a femoral and sciatic motor nerve block in patients undergoing primary TKA.
Keywords: primary TKA; opioid use; length of stay; femoral sciatic nerve block; adductor canal block; IPACK block